The Nutri-Score nutrition label - Hercberg, Serge (2022)
Rito Ana Isabel, Researcher, Director of Centre for Studies and Research on Social Dynamics and Health (CEIDSS), Lisbon, Portugal; Departamento de Alimentação e Nutrição, INSA, Lisbon, Portugal